Greeks and Barbarians Networking on the Shores of the Black Sea and Beyond : ἘΠΙΣΚΎΘΙΣΟΝ: Studies Presented to ASKOLD IVANTCHIK on his Sixtieth Birthday, May 2, 2025 - Ivanova, Anna; Mordvintseva, Valentina; Smirnov, Svyatoslav (Classical Studies E-Books Online, Collection 2025., 2025)
This volume presents contributions in honour of Askold Ivantchik on his sixtieth birthday. Since his main academic interest lies in the Black Sea region in ancient times inhabited by diverse cultural groups who also had frequent contacts with people from far beyond, we collected articles on this topic. The volume presents papers analyzing different kinds of sources and using various approaches to reveal networking and agency of peoples that belong to different social strata and cultural milieus. It will be of interest for scholars looking for multidisciplinary research methods as well as for the newest information about the archaeology of the Circumpontic region.